2004
DOI: 10.1016/j.jasms.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization tandem mass spectrometry and post-source decay fragmentation study of phenylhydrazones of N-linked oligosaccharides from ovalbumin

Abstract: N-linked oligosaccharides were released from hen ovalbumin by PNGase F and derivatized with phenylhydrazine. They were then examined by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. Phenylhydrazones of N-glycans under MALDI-tandem mass spectrometry (MS/MS) and post-source decay (PSD) conditions produced relatively similar fragmentation patterns; however, more cross-ring cleavages and fragment ions corresponding to low abundance isomeric structures were detected by MS/MS and not in PSD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 40 publications
5
50
0
Order By: Relevance
“…In our previous recent articles we introduced development phenylhydrazine (PHN) derivatization for labeling oligosaccharides from commercial sources [29,32]. The present study for the first time demonstrates application of this method for mass spectrometric analyses of carbohydrates from real complex biological material.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In our previous recent articles we introduced development phenylhydrazine (PHN) derivatization for labeling oligosaccharides from commercial sources [29,32]. The present study for the first time demonstrates application of this method for mass spectrometric analyses of carbohydrates from real complex biological material.…”
mentioning
confidence: 75%
“…Then, before each spot dried completely, PHN solution was spotted (0.5 L; 3 L of PHN reagent diluted in 12 L of deionized water and 3 L of ACN) and samples were left to dry at 37°C (ϳ30 min). MS/MS spectra of oligosaccharides were interpreted manually and detected structures of common N-glycan were compared with compositions described in previous studies [31][32][33]. For the assignment of all oligosaccharide fragment ions, the general nomenclature established by Domon and Costello was followed [34].…”
Section: Maldi-mass Spectrometric Analysismentioning
confidence: 99%
“…The low-energy CID spectrum displayed in Figure 2a was generated in the linear ion-trap instrument for the (GlcNAc) 6 (Man) 3 glycan structure (m/z 2153). It was previously shown that this structure consists of three isomeric glycan structures (denoted in different colors) depicted as I, II, and III in the inset of Figure 2a [62,63]. The most abundant product ion observed in the spectrum is m/z 1894, corresponding to the facile loss of GlcNAc (Nacetyl glucosamine) residue from the precursor.…”
Section: (A) (A) (B) (C) (D)mentioning
confidence: 90%
“…Symbols are the same as in Figure 1. companied by the following loss of water at m/z 694.2 45 could be assigned to the isomer with a branched antenna on 3-linked core mannose (1).…”
Section: Maldi-ms Analysis Of N-glycans From Mcf-7 and Cemmentioning
confidence: 99%